Dampak Pemahaman Agama Ajaran Tarekat Tajul Al-Khalwatiyah Terhadap Masyarakat Di Desa Timbuseng Kecamatan Pattallassang - St. Nuriftita Lewa; Hasaruddin; Muh. Nurlatif (Jurnal Berita Sosial, 2024)
This Thesis Discusses “The Impact Of Understanding The Tajul Al-Khalwatiyah Tarekat Teachings On The Community In Timbuseng Village, Pattallassang District, Gowa Regency,” With The Aim Of Finding Out: 1) The Essence And Practice Of The Impact Of Understanding The Tajul Al-Khalwatiyah Tarekat Teachings In Timbuseng Village, And 2) The Community’s Attitude Towards The Impact Of Understanding The Teachings. This Study Uses A Qualitative Method With Informants From The Timbuseng Village Community And Followers Of The Tarekat. The Results Of The Study Show That The Tajul Al-Khalwatiyah Teachings Emphasize The Concept Of Wihdatul Wujud, Namely The Belief That Only Allah Truly Exists. This Teaching Also Includes The Use Of Verses From The Qur’an, The Three Creeds, And The View That Allah Is Present During Prayer. The Community Gave Various Responses To This Teaching, With Some Feeling Disturbed By Religious Practices That Were Considered To Deviate From Traditional Islamic Teachings. This Study Highlights The Importance Of Tolerance And Correct Understanding Of Religion To Maintain Social Harmony, As Well As Reminding Us Of The Dangers Of Understanding That Deviates From The Teachings Of The Religion They Adhere To.